Ββ-lactams against emerging 'superbugs'': progress and pitfalls. Issue 4 (July 2008) - Skalweit Helfand, Marion
Bacterial resistance to antimicrobial agents is an ever-growing problem. So-called 'superbugs'', such as multidrug-resistant Acinetobacter baumannii and Pseudomonas aeruginosa harboring multiple resistance determinants, including extended-spectrum ββ-lactamases, carbapenemases, efflux pumps and downregulated outer-membrane proteins or porins, are becoming more prevalent in hospital, intensive and long-term care settings. Enterobacteriaceae are also acquiring a myriad of ββ-lactamases, such as class A and D carbapenemases, and plasmid-borne class C cephalosporinases. Gram-positive superbugs, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-intermediate or heteroglycopeptide-intermediate S. aureus, vancomycin-resistant S. aureus and penicillin-resistant Streptococcus pneumoniae (PRSP), are problematic pathogens, both in the hospital and in the community (e.g., community-acquired MRSA and PRSP). ββ-lactam antibiotics remain among the most effective and safest anti-infectives in use, although their utility is being severely challenged by these superbugs. This review will discuss aspects of resistance seen in these pathogens and will review some of the newer ββ-lactam agents, both investigational and in clinical use, that target these superbugs.